AN INTERPERSONAL COMMUNICATION IN DIGITAL-BASED PUBLIC SPACES: SELF-DISCLOSURE ANALYSIS IN BAGISUARA PODCASTS - Sarah Putri Auliya (Metakom, 2020)
Podcast s are one form of audio content that is more accessible to people because of the variety of content and flexibility of access. One popular podcast in Indonesia is BagiSuara. BagiSuara is a podcast that forms dialogue, so it becomes more than one party conducting communication activities. This study tries to analyze self-disclosure in BagiSuara podcast s. The concepts and models that are relevant for this research are interpersonal communication and self-disclosure. The main focus of this research is analyzing self-disclosure in the BagiSuara podcast . This research was conducted with a qualitative method using phenomenology. The results of this study provide an explanation of the openness of the parties conducting communication activities in the BagiSuara podcast.